2017
DOI: 10.1016/j.wem.2017.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Coagulopathy, Ecchymoses, and Microangiopathic Hemolytic Anemia Following Hump-Nosed Pit Viper (Hypnale hypnale) Bite in Sri Lanka

Abstract: A 74-year-old previously healthy woman was bitten by a hump-nosed pit viper (Hypnale hypnale) at dusk causing incoagulable blood lasting for 6 days. Further, she developed ecchymoses over her forearms, upper arms, hands, and lower back on day 4 after the snakebite, and microangiopathic hemolytic anemia (MAHA). Features of this nature are rare after hump-nosed pit viper bite.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Namal Rathnayaka et al 22 described Hypnale coagulopathy presenting as prolonged coagulopathy along with ecchymosis and microangiopathic haemolytic anaemia following H. hypnale bite. It is interesting to note that this is not a common feature seen in other viper envenomation.…”
Section: Microangiopathic Haemolytic Anaemiamentioning
confidence: 99%
“…Namal Rathnayaka et al 22 described Hypnale coagulopathy presenting as prolonged coagulopathy along with ecchymosis and microangiopathic haemolytic anaemia following H. hypnale bite. It is interesting to note that this is not a common feature seen in other viper envenomation.…”
Section: Microangiopathic Haemolytic Anaemiamentioning
confidence: 99%
“…Although local envenoming occurs more frequently after Hypnale bites, 8 -11 systemic effects such as AKI, CKD, 12,13 VICC, 2,14 -16 thrombotic microangiopathy (TMA), 13,17,18 ischemic strokes, 19 myocardial infarction, atrial fibrillation, and cardiac arrest 4,20 have also been reported. Of the 3 species, H hypnale 10,11,16,21 and H zara 2,11,18 cause VICC, but such complications have not so far been reported after H nepa bites.…”
Section: Introductionmentioning
confidence: 99%
“…16 Most commonly, hump-nosed pit vipers cause local envenoming effects such as pain, swelling, hemorrhagic blistering, and necrosis 10,17,18 and rarely systemic manifestations like coagulopathy, acute kidney injury, and chronic kidney disease. 10,19,20,21 MAHA associated with thrombotic microangiopathy is a well-known complication after viperidae snakebites, including hump-nosed pit vipers 8,22,23 and Russell's vipers (Daboia russelii). 24 The pathophysiology of MAHA is due to damage of the endothelial layer of small blood vessels with resulting fibrin deposition and platelet aggregation.…”
Section: Discussionmentioning
confidence: 99%